Taking inventory of Orchid Types in a Region of Tambora Mountain - Sumbawa Island - Wibawa, I Putu Agus Hendra; Peneng, I Nyoman; Priyadi, Arief (Proceeding International Conference on Global Resource Conservation, 2013)
Indonesia is well known as one of the countries with high biodiversity in the world, including its orchids. It is expected that there are 6,000 kinds of orchids which grow wildly in forest regions around the world. Along with accelerated forest destructions in Indonesia, due to land conversions or natural disasters, the existence of orchids in their natural habitats is threatened. It is likely that some of these richness could be lost before they can be conserved and known of their functions. Regions of Tambora mountain in Sumbawa island have biodiversity that had not been revealed. Therefore, taking inventory of flora in that region is very crucial to be done as soon as possible. This activity was aimed at saving biodiversity especially rare and endemic orchids there, and also quantitatively knowing richness and frequency of orchids species which are found. From the research, it is known that there were 22 orchids species, from which only one is terrestrial and the rests are epiphytes. In terms of richness, there were some orchids which were common and also rare.Â Keywords: orchids, Tambora Mountain, conservation, exploration